ICT and metalinguistic competence: Developing phonetic transcription skills through regular expressions - Jacopo Saturno (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication, 2023)
The present paper describes an applied linguistics experiment aiming to evaluate the appropriateness of regular expressions (regex) to improve foreign language students' ability to identify the relationship between the graphic (letters) and phonic (phonemes) units of a language. Since the focus of the study is on metalinguistic rather than linguistic skills, the native language of the participants–L1 Italian–was chosen to this purpose. Specifically, regexes were used to formalise the phonological transcription rule of a set of graphemes (eg /ʃa/) well known for causing transcription errors due to the interference of orthography. Both before (T1) and after (T2), the regex formalisation task, 255 university students of foreign languages were asked to verbally explain the relevant transcription rules and transcribe a set of words containing the grapheme of interest. The results show that indeed, the accuracy of transcriptions and metalinguistics accounts significantly improved after the task. A discussion of the possible applications of regexes in the training of students of foreign languages and linguistics concludes the paper.